Supervisi Akademik Kepala Sekolah dalam Peningkatan Mutu Pembelajaran Guru di SMP Muhammadiyah Balikpapan - Rohana Rohana; Rahmat Soe’oed; Azainil Azainil (Journal on Education, 2023)
Academic supervision is a process taken by school principals to help teachers improve their ability to manage effective learning. This study aims to determine the planning, implementation, evaluation, follow-up, constraints, and solutions in the academic supervision of school principals in an effort to improve the quality of teacher learning at SMP Muhammadiyah Balikpapan. This study uses a descriptive method with a qualitative approach. Data collection techniques using interviews, observation, and documentation. Principals, vice principals, and teachers participated in this study. Data analysis was carried out through the stages of reduction, presentation, and drawing conclusions. The results of this study found that planning for the principal's academic supervision begins with holding meetings with teachers to develop regular programs and prepare supervision instruments. The implementation of academic supervision is carried out through class observation by observing the implementation of learning, starting from the teacher opening the lesson to closing the lesson, establishing communication between the principal and the teacher to provide input, discussing and sharing information between teachers so that the teacher can improve his quality and master the learning process in the classroom.